OPTIMIZING FAMILY EMPOWERMENT IN IMPROVING KNOWLEDGE AND BEHAVIOR AS PREVENTION OF RECURRENT STROKE - Septianingrum, Yurike; Sari, Ratna Yunita; Hatmanti, Nety Mawarda; Wijayanti, Lono; Imamatul, Faizah; Yuniati, Dyah (Journal of Indonesian Public Health Service, 2025)
Family as an informal caregiver has a very important role in the care of stroke patients. Families do not have sufficient knowledge and skills in caring for stroke patients because they are not trained. Families actively involved in care will feel more prepared to face new responsibilities in caring for stroke patients. This community service activity aims to improve knowledge and behavior to prevent recurrent stroke. The method used in this community service activity is a participatory education approach, including educational methods using the stroke self-management education module. This activity was conducted in May 2024 at RW 07, Banyu Urip Village, Surabaya. It was attended by 20 families of stroke patients. Evaluation of knowledge using the recurrent stroke prevention knowledge questionnaire and behavior using the stroke patient care behavior questionnaire. The community service results showed that family caregivers' knowledge and behavior increased after the family empowerment program. Family empowerment can improve knowledge and behavior in family caregivers of stroke patients in preventing recurrent stroke. Family empowerment programs can be provided periodically by community nurses to improve the ability of family caregivers to improve the quality of life of stroke patients.